The impact of technological and social capabilities on innovation performance: a technological catch-up perspective. (February 2022) - Fakhimi, MohammadAmin; Miremadi, Iman
Abstract: The literature on technological capabilities has highlighted the effects of innovation on economic growth. However, further analysis is required to determine how innovation factors affect the technological catch-up process outputs. The main purpose of the present study is therefore to determine the impacts of innovation-building factors (i.e., technological and social capabilities) on the innovation outputs. The role of market and innovation financing in technological catch-up has also been investigated. Partial least squares structural equation modeling has been employed to identify which factors have the most significant effects on this process. We have extracted twelve hypotheses from the catch-up theory and then investigated the effects of the factors on the outputs in seventy countries during 2013–2019. The results illustrate that human capital and research are influential factors regarding technological catch-up in middle (and upper-middle) income countries. Relationships between academic and industrial sectors are essential for educational and research expenditures. Furthermore, business sophistication has a more significant effect on high-income countries rather than middle-income countries. Highlights: Technological and social capabilities play a key role in innovation performance at national level. The impacts of innovation-building factors on the innovation outputs is presented. Partial least squares structural equation modeling has been employed to identify which factors have most significant effects. Results illustrate that human capital and research are crucial factors on technological catch-up in middle-income countries. Relationships between academic and industrial sectors are essential for educational and research expenditures.